2018
DOI: 10.1021/acschemneuro.8b00138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Alkyl-4-Methylamphetamine Optical Isomers on Plasma Membrane Monoamine Transporters and Abuse-Related Behavior

Abstract: 4-Methylamphetamine (4-MA) is an emerging drug of abuse that acts as a substrate at plasma membrane transporters for dopamine (DAT), norepinephrine (NET), and serotonin (SERT), thereby causing non-exocytotic release of monoamine transmitters via reverse transport. Prior studies by us showed that increasing the N-alkyl chain length of N-substituted 4-MA analogs converts 4-MA from a transportable substrate (i.e., releaser) at DAT and NET to a non-transported blocker at these sites. Here we studied the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 34 publications
2
26
1
Order By: Relevance
“…In the Ca 2+ assay, N-methyl-4-MA produced Ca 2+ signals in cells expressing each of the transporters, indicating that N-methyl-4-MA is a releaser (or substrate) at the three MATs (Solis et al 2017). As expected, S(+) and racemic N-methyl-4-MA showed potent release activity at all three MATs as measured in synaptosomes and in the Ca 2+ assay (Battisti et al 2018). To assess the abuse-related effects of this drug in vivo, it was tested in ICSS studies.…”
Section: Validation Of Ca 2+ -Based Biosensors To Characterize Ligands Of Monoamine Transporterssupporting
confidence: 69%
“…In the Ca 2+ assay, N-methyl-4-MA produced Ca 2+ signals in cells expressing each of the transporters, indicating that N-methyl-4-MA is a releaser (or substrate) at the three MATs (Solis et al 2017). As expected, S(+) and racemic N-methyl-4-MA showed potent release activity at all three MATs as measured in synaptosomes and in the Ca 2+ assay (Battisti et al 2018). To assess the abuse-related effects of this drug in vivo, it was tested in ICSS studies.…”
Section: Validation Of Ca 2+ -Based Biosensors To Characterize Ligands Of Monoamine Transporterssupporting
confidence: 69%
“…In the present study, SRI-31142 effects on DAT function were further evaluated using imaging procedures to assess DAT-mediated fluorescent signals in live cells. Previous studies have shown a high correlation between drug effects in rat brain synaptosomes and in this assay of DAT-mediated fluorescent signals (Solis et al, 2017;Battisti et al, 2018); however, SRI-31142 effects were not consistent across assays. Specifically, in contrast to findings in rat brain synaptosomes, SRI-31142 failed to produce a cocaine-like blockade of DAT-mediated fluorescent signals.…”
Section: Discussioncontrasting
confidence: 56%
“…Accordingly, SRI-31142 pharmacokinetics in rats were assessed to evaluate the adequacy of brain penetration. Additional studies on SRI-31142 pharmacodynamics were also conducted to examine possible off-target binding sites (Besnard et al, 2012) and the effects on DAT-mediated Ca 21 fluorescence and APP 1 uptake in live cells (Solis et al, 2017;Battisti et al, 2018). Overall, our results suggest that SRI-31142 does not produce abuse-related behavioral or neurochemical effects and that it attenuates cocaine effects by acting via a non-DAT mechanism of action.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations